Impact of Virtual Worlds on Student Engagement and Academic Performance: An Analysis of Online Learning Using Second Life Technology - As, Mansur; Fauziyah Harahap; Sitti Subaedah; Tsunenori Mine; Mario Köppen (Journal of Soft Computing and Data Mining, 2024)
The metaverse is a virtual world with immense potential and is increasingly adopted as an online learning platform for students. Students can build virtual worlds that simulate real-life experiences using interactive activities. In this study, we implemented student learning in the virtual world and evaluated the effects of students’ achievements. Online learning formats were conducted in Second Life (SL) technology for one semester by three groups (classes), and the data was collected, including several categories, i.e., project work, interaction logs, feedback forms, online quizzes, and attendance. We then employed the robust Multiple Linear Regression (MLR) technique to classify student performance during their virtual learning experience. The results showed significant improvements in student learning across several categories, with substantial variations observed among the different classes. Interestingly, we also found that students in each class had unique experiences and faced distinct challenges in the virtual learning environment.